CLARITHROMYCIN IN TREATMENT OF TONSILLITIS IN CHILDREN - Yu. L. Soldatskii (Вопросы современной педиатрии)
Acute tonsilittis and episodes of chronic tonsilittis relapses are the most common infectious inflammatory diseases of the throat. A significant risk of development of different organs diseases associated with tonsilittis and worsening of the life quality in a patient with soar throat cause the currency of the rational antibacterial treatment. A special feature of tonsilittis in children is a high prevalence of viral and atypic diseases. A possibility of clarithromycin usage as a first-line drug in empiric systemic antibacterial treatment of acute tonsilittis is analysed in this article.